1985
DOI: 10.1128/iai.48.2.324-330.1985
|View full text |Cite
|
Sign up to set email alerts
|

Composition and antigenic activity of the oligosaccharide moiety of Haemophilus influenzae type b lipooligosaccharide

Abstract: The oligosaccharide moiety of the lipooligosaccharide of Haemophilus influenzae type b strain Eag was isolated from the lipid component by mild acid hydrolysis and purified by gel filtration. Fast atom bombardment-mass spectrometry indicated that the lipid-free oligosaccharide had a basic molecular weight of 1,768; polysaccharides comparable to high-molecular-weight 0 side chains were not found. Glucose, galactose, galactosamine, heptose, 3-deoxy-D-manno-2-octulosonic acid (KDO), ethanolamine, and phosphate we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…The CP was purified as previously describe (10). LPS was extracted with hot 45% phenol and purified by ultracentrifugation as previously described (11,35).…”
Section: Methodsmentioning
confidence: 99%
“…The CP was purified as previously describe (10). LPS was extracted with hot 45% phenol and purified by ultracentrifugation as previously described (11,35).…”
Section: Methodsmentioning
confidence: 99%
“…Relatively little is known about the physical structure of Hib LOS. Biochemical analysis has indicated that the oligosaccharide moiety of Hib LOS contains several different (20,30,45). The LOS of Hib also appears to be relatively high in phosphate content (45).…”
Section: Discussionmentioning
confidence: 99%
“…Complexes of lipopolysaccharide to polymyxin-B were also prepared (4,48). The lipid A fractions from the monkey isolate of P. gingivalis, B. forsythus (strain #9610) and A. actinomycetemcomitans (strain Y4) were prepared by mild acetic acid hydrolysis of hpopolysaccharide, centrifugation and chloroform extraction (15,24). The fatty acid and sugar composition of lipopolysaccharide and lipid A preparations were determined by gas-liquid chromatography with a Hewlett-Packard #5890 system equipped with an HP-1 capillary column by the method of Bryn & Jantzen (6) as described previously (41).…”
Section: Antigen Preparationsmentioning
confidence: 99%